EFEKTIVITAS PELAYANAN PESAK MERA OLEH DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN BANGKALAN - Novendra Vigo Ramadhani; Ananta Prathama (Journal Publicuho, 2024)
This research aims to find out, analyze, and explain the effectiveness of the Pesak Mera program organized by Dispendukcapil Bangkalan. The focus of this research uses aspects, including resources, funds, facilities and infrastructure; the quantity and quality of services produced; the predetermined time limit; and the service procedures that must be taken. This research uses a descriptive qualitative approach with data collection techniques using interviews, documentation, and field observations. The results show that the effectiveness of the Pesak Mera program organized by Dispendukcapil Bangkalan has been running effectively in accordance with the program's objectives. Resources, facilities, and funds have been well fulfilled, although there are still obstacles in facilities and infrastructure when there is a power outage, but such incidents are very rare. The quantity and quality of services produced have increased, including the number of population and civil registration services. The predetermined time limit has been successfully met, which is directly proportional to the upward trend in the number of services. The service procedures that must be taken have not changed much, except for the addition of door-to-door and pick-up services.